Answer:
![y=-4x+17](https://tex.z-dn.net/?f=y%3D-4x%2B17)
Step-by-step explanation:
![\begin{pmatrix}4&1\end{pmatrix}\quad \mathrm{and}\quad \begin{pmatrix}2&9\end{pmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bpmatrix%7D4%261%5Cend%7Bpmatrix%7D%5Cquad%20%5Cmathrm%7Band%7D%5Cquad%20%5Cbegin%7Bpmatrix%7D2%269%5Cend%7Bpmatrix%7D)
![\mathrm{Computing\:dot\:product\:of\:two\:vectors}:\quad \left(x_1,\:\:\ldots ,\:\:x_n\right)\cdot \left(y,\:\:\ldots ,\:\:y_n\right)=\sum _{i=1}^nx_iy_i](https://tex.z-dn.net/?f=%5Cmathrm%7BComputing%5C%3Adot%5C%3Aproduct%5C%3Aof%5C%3Atwo%5C%3Avectors%7D%3A%5Cquad%20%5Cleft%28x_1%2C%5C%3A%5C%3A%5Cldots%20%2C%5C%3A%5C%3Ax_n%5Cright%29%5Ccdot%20%5Cleft%28y%2C%5C%3A%5C%3A%5Cldots%20%2C%5C%3A%5C%3Ay_n%5Cright%29%3D%5Csum%20_%7Bi%3D1%7D%5Enx_iy_i)
![=4\cdot \:2+1\cdot \:9](https://tex.z-dn.net/?f=%3D4%5Ccdot%20%5C%3A2%2B1%5Ccdot%20%5C%3A9)
![=17](https://tex.z-dn.net/?f=%3D17)
Answer:
500$
finaced= provide funding for
Answer:
if y is -2, your answer is x = -1
if x is -2, your answer is y = -4
Step-by-step explanation:
If x is -2,
y = 2 (-2)
y = -4
<em><u>But</u></em>
If y is -2
-2 = 2x
x = -2/2
x = -1
If you are satisfied with my answer please make it the brainliest.
2(4-3x) is the answer to X2+(-x)+(-3x2)+(-5x)+12